Empirical Linear Seismic Site Amplification in Central and Eastern North America. Issue 2 (May 2019) - Parker, Grace A.; Stewart, Jonathan P.; Hashash, Youssef M. A.; Rathje, Ellen M.; Campbell, Kenneth W.; Silva, Walter J.
We present empirical linear site amplification models conditioned on time-averaged shear wave velocity in the upper 30 m ( VS 30 ) for central and eastern North America. The models are derived from ground motion data and site condition information from the NGA-East project and are intended for use with reference rock ground motion models. Site amplification is found to scale with VS 30 for intermediate to stiff site conditions ( VS 30 > 300 m/s) in a weaker manner than for active tectonic regions such as the western United States. For stiff sites ( > 800 m/s), we find differences in site amplification for previously glaciated and nonglaciated regions, with nonglaciated sites having lower amplification. The models were developed using a combination of least-squares, mixed effects, and Bayesian techniques; the latter show that accounting for predictor uncertainty does not appreciably affect the median model but decreases model dispersion. Our VS 30 -scaling models are modular and additive to simulation-based models for the nonlinear components of site response. A limitation of the present models is that they do not account for site-specific resonance effects.